Presenting a Proper Ensemble Clustering (EC) Method Based on Hierarchical Methods and Classical Generative Algorithms - Zahra Sahebkaram; Alireza Norouzi (Majlesi Journal of Electrical Engineering)
Ensemble Clustering (EC) methods became more popular in recent years. In this methods, some primary clustering algorithms are considered to be as inputs and a single cluster is generated to achieve the best results combined with each other. In this paper, we considered three hierarchical methods, which are single-link, average-link, and complete-link as the primary clustering and the results were combined with each other. This combination was done based on correlation matrix. The basic algorithms were combined as binary and triplicate and the results were evaluated as well. the IMDB film dataset were clustered based on existing features. CH, Silhouette and Dunn Index criteria were used to evaluate the results. These criteria evaluate the clustering quality by calculating intra-cluster and inter-cluster distances. CH index had the highest value when all three basic clusters are combined. our method shows that EC can achieve better results and present clusters with higher robustness and accuracy.